KEBIJAKAN PENGAWASAN DAN PENGENDALIAN PENDUDUK: Era Otonomi Khusus Di Provinsi Papua - La Pona La Pona; Wellem Rumpampam (JURNAL KEBIJAKAN PUBLIK, 2018)
The provincial government is currently processing the document of the Governor of the Regulation and Control of Population growth in Papua province. Human Resources Development Agency (BPSDM) Papua province is doing some work programs in order to prepare and establish regulations in question. Population policy is an implementation of Law No. 21 of 2001 on Special Autonomy for Papua Province and Papua Provincial Regulation (Perdasi) No. 15 of 2008 on population. The focus of this rule is more dominant set the field of migration as the dominant factor causing population growth in Papua. It is planned that this rule would regulate the field of birth and death also, because in theory the cause of population growth is not only influenced the migration aspects but also aspects of death and rebirth. The difference between outmigration and inmigration is net migration. If inmigration then the addition of more residents in the region, and vice versa. If born population more than the death of the accretion occurs naturally (natural increase of), and vice versa, so regulation of the Governor's supervision and control of population growth should regulate the field of migration, births and deaths of the population.